Diagnóstico das bibliotecas especializadas da administraç\~ao pública federal brasileira - Elaine Coutinho Marcial; Jhonathan Divino Ferreira dos Santos Santos; Jeanluiz Ferreira Porto Monteiro; Carolina Gonzalez; Josina da Silva Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The specialized libraries of the federal public administration provide services for the keeping and preservation of institutional memory, as well as meeting the specialized information needs of their maintainers, providing informational subsidies for the decision-making and public policy-making processes, as well as disseminating knowledge generated, both within the state and in society. Taking into account the strategic character that information production, management, preservation and dissemination activities have and their impact on state efficiency and transparency, it is necessary to know and to study these libraries. In this context, the objective of this research is to identify the profile of these libraries, verifying their role in their supporting institutions in relation to information management and strategic decision support, presenting the innovations promoted and proposing solutions to the identified problems. An in-depth investigation of the libraries of the federal public administration is carried out here, seeking to fill in gaps regarding the understanding of the past and the present, which we consider essential to think about the future of these libraries.To this end, it was conducted a study of the evolution of the characteristics and management of these libraries face the technological advances, considering the administrative reforms of the state. The study was conducted with the application of questionnaire to a target population of specialized libraries formed federal public administration packed in Brasilia, seeking the census and data analyzed by using descriptive statistics. The results indicate that many libraries do not occupy strategic space in the State, even in the context of the information and knowledge society. Given the State's need to preserve institutional memory and enjoy adequate information services to support strategic decisions, it is necessary to create an information policy that guides all information management work within the State, including the work of these libraries.
Keywords: M19; 330; specialized libraries; federal public administration; diagnostics